Multidrug-resistant pathogenic Escherichia coli isolated from wild birds in a veterinary hospital. Issue 1 (2nd January 2017) - Borges, C. A.; Beraldo, L. G.; Maluta, R. P.; Cardozo, M. V.; Barboza, K. B.; Guastalli, E. A. L.; Kariyawasam, S.; DebRoy, C.; Ávila, F. A.
ABSTRACT: Wild birds are carriers of Escherichia coli . However, little is known about their role as reservoirs for extra-intestinal pathogenic E. coli (ExPEC). In this work we investigated E. coli strains carrying virulence genes related to human and animal ExPEC isolated from free-living wild birds treated in a veterinary hospital. Multidrug resistance was found in 47.4% of the strains, but none of them were extended-spectrum beta-lactamase producers. Not only the virulence genes, but also the serogroups (e.g. O1 and O2) detected in the isolates of E. coli have already been implicated in human and bird diseases. The sequence types detected were also found in wild, companion and food animals, environmental and human clinical isolates in different countries. Furthermore, from the 19 isolates, 17 (89.5%) showed a degree of pathogenicity on an in vivo infection model. The isolates showed high heterogeneity by pulsed-field gel electrophoresis indicating that E. coli from these birds are clonally diverse. Overall, the results showed that wild birds can be reservoirs and/or vectors of highly pathogenic and multidrug-resistant E. coli that have the potential to cause disease in humans and poultry.